Back Cover: Highly Luminescent One‐Dimensional Organic–Inorganic Hybrid Double‐Perovskite‐Inspired Materials for Single‐Component Warm White‐Light‐Emitting Diodes (Angew. Chem. Int. Ed. 2/2023). Issue 2 (15th December 2022) - Bai, Tianxin; Wang, Xiaochen; Wang, Zhongyi; Ji, Sujun; Meng, Xuan; Wang, Qiujie; Zhang, Ruiling; Han, Peigeng; Han, Ke‐li; Chen, Junsheng; Liu, Feng; Yang, Bin
Abstract : Double perovskites are one of the most promising candidates for developing white‐light‐emitting diodes owing to their intrinsic broadband emission from self‐trapped excitons. In their Research Article (e202213240), Feng Liu, Bin Yang, and co‐workers report a novel highly luminescent one‐dimensional double‐perovskite‐inspired material with a warm‐white photoluminescence quantum yield of 92 %. Furthermore, single‐component warm‐white light emitting diodes were fabricated by using this material.